PENGARUH MEDIA GANTUNG SUSUN TERHADAP HASIL BELAJAR SISWA PADA MATERI MENENTUKAN NILAI TEMPAT DI TINGKAT SEKOLAH DASAR - Anisatul Karimah; Raudatul Hasanah (JEMI, 2024)
This study aims to determine the effect of media usage of hanging stack to the result of learning mathematics material determining the value of place of hundreads, tens and units of class II SDN Pabian III Sumenep. This research is motivated by result of student’s mathematics learning whics is still under KKM. This research is a quantitative research using true experimental design type control group pre-test-post-test methode. This study used two groups of experimental groups treated using suspended hanging media and control groups without treatment. The variables of this study consist of independent variables that are the use of hanging media stacking while the dependent variable is the result of learning mathematics in determining the value of place hundreads, tens, dan units. This reserach is a populative research with the total number of students of class II as many as 36 students. The instrument used in this research is a test question. Data analysis technique in this research use t-test. The result of this study indicate that there is influence of media usage of hanging stack to the result of learning mathematics to determine the value of palace of hundreds, tens and unit in second grade student of SDN Pabian III Sumenep. This is evidenced by the result of t-test calculation showing that there is a difference in the post-test result of the experimental group with the control group. Result of t-test calculation is tcount, the value equal to -2,346 with significance level 0.025. based on the table, the value of t for df = 34 is -2,028 (-2,346 < -2,028 <2,028). From the analysis it is found that thitung>ttabel